2005
DOI: 10.1152/ajpregu.00680.2004
|View full text |Cite
|
Sign up to set email alerts
|

Social environment modulates photoperiodic immune and reproductive responses in adult male white-footed mice(Peromyscus leucopus)

Abstract: Social cues may interact with photoperiod to regulate seasonal adaptations in photoperiod-responsive rodents. Specifically, photoperiod-induced adjustments (e.g., reproduction and immune function) may differ among individuals in heterosexual pairs, same-sex pairs, or isolation. Heterosexual cues may be more influential, based on their potential fitness value, than same-sex cues or no social cues. The present study examined the effects of pair (with a male or female) or individual housing on reproductive and im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 36 publications
3
22
0
Order By: Relevance
“…Indeed, reports of male P. polionotus intromission latencies in tests with hormone primed females are six times longer than those observed for P. maniculatus (Dewsbury, 1971). A study on P. leucopus reported that males paired with ovariectomized females in long days had higher T than single housed males (Pyter et al, 2005b). Presumably these males did not mate with their female cagemates.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Indeed, reports of male P. polionotus intromission latencies in tests with hormone primed females are six times longer than those observed for P. maniculatus (Dewsbury, 1971). A study on P. leucopus reported that males paired with ovariectomized females in long days had higher T than single housed males (Pyter et al, 2005b). Presumably these males did not mate with their female cagemates.…”
Section: Discussionmentioning
confidence: 95%
“…At a neuroendocrine level, photostimulation of male hamsters with long days triggers an FSH surge within 3-5 days (Wolfe et al, 1995), but an LH surge is delayed unless hamsters are simultaneously housed with a female (Anand et al, 2002). In white-footed mice (Peromyscus leucopus), photoperiod has similar contextdependent effects; males paired with ovariectomized females for 13 weeks increased testes mass in long day conditions compared to individually-housed males, but pair-housing did not affect testes mass in short days (Pyter et al, 2005b).…”
Section: Introductionmentioning
confidence: 99%
“…Some rodents also allocate to immune defence differently depending on latitude. Aztec mice (Peromyscus aztecus), which reside in southern Mexico, show no immunological responsiveness to the changes in day length , whereas more northerly distributed species (northern USA) show enhanced responses in short days coupled with reduced responses in long days when breeding typically occurs (Pyter et al 2005a). Recent work in meadow voles (Microtus pennsylvanicus) indicates that the effects of latitude on immune activity may be complicated in some cases.…”
Section: K1mentioning
confidence: 99%
“…All mice were sensitized to 2, 4-dinitro-1-fluorobenzene (DNFB; Sigma-Aldrich, St. Louis, MO, USA) by applying 50μL of DNFB [0.5% (w/v) in 4:1 acetone/olive oil vehicle] to a shaved area on the rump for two consecutive days while each mouse was under anesthesia (isoflurane in O 2 enriched-air) (Pyter et al 2005b;Martin et al 2006b). One week later, mice were again anesthetized, and thicknesses of pinnae were measured using a constant-loading micrometer (Mitituyo, Tokyo).…”
Section: Delayed-type Hypersensitivity (Dth)mentioning
confidence: 99%
“…We assessed effects of 6-MBOA on reproductive parameters and DTH in long-day breeding whitefooted mice. This species was chosen because individuals i) exhibit seasonal changes in immune activity and reproductive capacity (Johnston et al 1980b;Pyter et al 2005b), ii) some of these changes are mediated by melatonin (Johnston et al 1980a;Glass et al 1988), and iii) individuals consume a variety of foods in the wild, including plants (King 1968). Other species known to be sensitive reproductively to 6-MBOA have not been as well characterized.…”
Section: Introductionmentioning
confidence: 99%